Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Okay, these get easy with practice so don't post all of these online. First, substitute y in 3x-2y=9 for what it says y equals (2x-7). You now have: 3x-2(2x-7)=9. Breakdown:
3x-2(2x-7)=9
3x-4x+14=9
-1x=-5
x=5
next solve for y
y=2x-7
y=2(5)-7
y=10-7
y=3
And now we have x=5, and y=3.
3x-2(2x-7)=9
3x-4x+14=9
-1x=-5
x=5
next solve for y
y=2x-7
y=2(5)-7
y=10-7
y=3
And now we have x=5, and y=3.
Since you know that "y" is equivalent to "2x - 7" you can substitute that into the first equation
3x - 2y = 9
3x - [2(2x-7)]= 9
3x - (4x - 14) = 9
3x - 4x + 14 = 9
-x + 14 = 9
-x = -5
x = 5
y = 2x - 7
y = 2(5) - 7
y = 10 - 7
y = 3
3x - 2y = 9
3x - [2(2x-7)]= 9
3x - (4x - 14) = 9
3x - 4x + 14 = 9
-x + 14 = 9
-x = -5
x = 5
y = 2x - 7
y = 2(5) - 7
y = 10 - 7
y = 3
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.